Kelayakan Limbah Sisik Ikan Nila Menjadi Produk Kreatif Aksesoris Nail Art - Salsa Alya Mafaza; Ifa Nurhayati; Godham Eko Saputro (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to determine the feasibility of tilapia scale waste as a basic material for making nail art accessories that have economic and environmentally friendly value. The research was carried out at Nail's By Valeta, Pakintelan, Gunung Pati District, Semarang City using a quantitative descriptive approach through the experimental one-shot case study method. The test was carried out through two stages, namely the product validity test by three expert judgments and the preference test by 30 trained respondents. The results of the validity test showed that nail art accessories products obtained an average score of 94.3% with the category "very valid". This is because almost all aspects of the assessment starting from shape, neatness, strength, color, and finish have met the standards set by the validator. Meanwhile, the results of the liking test obtained an average score of 96% with the category "Very Like", this is because almost all aspects of the assessment ranging from shape, strength, aesthetics, neatness, convenience, and final results have met the standards set by the respondents. These results prove that tilapia scales are suitable for use as an alternative material for making aesthetically attractive nail art accessories, easy to apply, and in accordance with beauty industry trends based on eco-friendly and sustainability. Thus, the use of tilapia scale waste has the potential to become an innovation in beauty products with high selling value while supporting the reduction of environmental waste.